PENERAPAN MODEL PEMBELAJARAN REALISTIC MATHEMATIC EDUCATION (RME) UNTUK MENINGKATKAN KERJASAMA DAN PRESTASI BELAJAR SISWA - Nova Anisna Desvita; Turdjai Turdjai (UNIB Press, 2020)
This study aims to (1) describe the application of Realistic Mathematic Education (RME) learning models to improve student collaboration, (2) describe the RME learning model to improve student achievement, (3) Effectiveness of the application of Realistic Mathematic Education (RME) learning to improve the results of student learning. This research was carried out using Classroom Action Research (CAR) and Quasi experiments. Data collection methods in this study use observation sheets to measure the ability of teachers to apply Realistic Mathematic Education (RME) learning models and student collaboration skills, as well as tests to measure improvement in student learning achievement. For data analysis the average score analysis and t-test were used. Based on the results of research that has been carried out as many as three cycles in MIPA 1 class Xl, this study produces conclusions: (1) the application of the Realistic Mathematic Education (RME) learning model can improve student collaboration skills, (2) the application of the Realistic Mathematic Education (RME) learning model can improve student learning achievement, (3) the application of learning models Realistic Mathematic Education (RME) effectively improves student learning outcomes in mathematics.